PENGGUNAAN INSTAGRAM SEBAGAI STRATEGI KOMUNIKASI PEMASARAN TOKO BUKET SBUKET.ID (KOMUNIKA BANGSA, 2023)
Selling bouquets using Instagram uses the 4P Marketing Mix concept, namely Promotion, Product, Price, & Place, to be interesting. For this reason, the research aims to find out the promotion strategy of Sbucket.id stores in marketing products to attract consumers' interest in buying via Instagram, and how sellers communicate selling prices to consumers, as well as strategic location which is a determining factor in consumer purchases. This research was located at the Sbucket.id Store in Lubuklinggau City, South Sumatra. The research method used is a qualitative research method. The informants in the research consisted of six people, namely the owner or owner of the Sbucket.id shop, the admin of Sbucket.id and also four consumers or buyers who had bought a bouquet at the Sbucket.id shop using data collection techniques through semi-structured interviews, observation non-participants and also documentation. From the research results, it can be seen that in order to attract consumers' interest in buying a bouquet at the Sbucket.id shop, they promote the product via Instagram social media, initially they use Endorsement services, then they always promote the product via Instagram Stories, and also upload photos of the bouquet on the Instagram feed. by adding a caption. Consumers can request a bouquet according to their wishes, so before purchasing it needs to be communicated first to the sbucket.id admin. The location of the Sbucket.id shop is very strategic, located on the side of the road and close to various schools so that consumers can easily find and reach the Sbucket.id shop location..Keywords: Marketing Communication, Instagram, BouquetsÂ